Emprego DAETV-ICP OES para a determinação de impurezas inorgânicas em produtos farmacêuticos - Kaczala, Suelem (2013)
In this study a method for As, Cd, Cr, Cu, Mn, Mo, Ni, Pb, Pd, Pt, Rh, Ru and V determination in pharmaceuticals products by electrothermal vaporization inductively coupled plasma optical emission spectrometry (ETV-ICP OES) was developed. The Brazilian Pharmacopoeia (FB) recommends acid digestion of the sample before element determination by atomic spectrometry. However, some pharmaceuticals, such as tricyclic compounds, are difficult to be decomposed by conventional acid digestion. In order to avoid the step of sample digestion, direct solid sample analysis by ETV-ICP OES is proposed. Electrothermal vaporization consists in vaporizing the sample to be introduced in the plasma. The influence of CCl2F2 as chemical modifier was investigated and 3.0 mL min-1 was considered the ideal flow rate. Modifier and carrier effect of ascorbic acid, citric acid, oxalic acid, ethylenediaminetetraacetic acid and sodium cloride was also evaluated. Vaporization and pyrolysis temperatures were adjusted in order to obtain a single temperature program for multielement determination by ETV-ICP OES. Hence, temperatures of 350 °C and 1600 °C were considered suitable for pyrolysis and vaporization, respectively. Sample mass was also evaluated and 2.5 mg was considered appropriate. By the proposed ETV-ICP OES method only Cr (5.5 μg g-1) was detected in cyclobenzaprine hydrochloride. Since there are not certified reference materials with similar matrix to the samples, accuracy was checked by comparison of results obtained by inductively coupled plasma mass spectrometry after microwave induced combustion. Agreement of 87% (by comparison with ICP-MS) and 91% (by analyte recovery) was obtained for Cr. The limit of quantification (10 σ, n = 10) of the proposed method was in the range of 0.08 μg g-1 for Mn and 356 μg g-1 for As, while the relative standard deviation (n = 3) was lower than 10%. The frequency of determination was 20 h-1. Considering the analytical characteristics the proposed method can be considered suitable for element determination in tricyclic pharmaceuticals.